Rubus oklejewiczii (Rosaceae), a new bramble species from Central Europe (Poland: Carpathians) - Wolanin, Mateusz M.; Musiał, Krystyna; Nobis, Marcin (Phytotaxa, 2020)
A new species from south-eastern Poland, named Rubus oklejewiczii Wolanin & M. Nobis, is here described and illustrated. It is pentaploid deciduous plant, with morphological features most typical to the species representing Rubus ser. Rubus. The species is distributed in the northern foreground of the Polish Carpathians and has been observed mostly in fir-beech forests margins.